Investigation of multiple cracking in glass/epoxy 2D woven composites by vibrothermography. Issue 1 (2nd January 2016) - Bai, Gabriele; Lamboul, Benjamin; Roche, Jean-Michel; Baste, Stéphane
Abstract : An experimental study about the application of vibrothermography for the investigation of multiple micro-cracking in woven composites is here reported. The material is first damaged during tensile loading tests in order to have samples that present increasingly damaged states. The goal of the study is to evaluate the sensitivity of the vibrothermographic effect to crack density. A linear correlation trend is observed on the tested samples between the measured heating during mechanical excitation and the crack density. A linear correlation trend is also observed between the heating and the loss of in mechanical property of the material (in this case the Young modulus).